Terahertz spoof plasmonic coaxial microcavity - Yu, Zaihe (2014)
We theoretically demonstrate a subwavelength spoof surface-plasmon–polariton (SPP) microcavity on a planar metallic surface working at the terahertz regime with a high-quality factor and ultra-small mode volume. The microcavity is based on plasmonic and metamaterial notions, and it consists of an easy-to-manufacture circular aperture and a bell-shaped metallic core. It is shown that such a structure can sustain SPP eigenmodes whose fields are tightly trapped within the microcavity. Using the proposed structure, a total Q factor of 1000 (including losses from metals at low temperatures) and subwavelength mode volume of 0.00018(λ/2)3 can be achieved in the THz range for the fundamental surface-plasmonic eigenmode at room temperature. Moreover, the key figures of merit such as resonance frequency can be flexibly tuned by modifying the geometry of the microcavity, making it attractive for broad applications in filters, light sources, energy storage, and on-chip optical communications.